New opportunities for nuclear cardiology with total-body positron emission tomography/computed tomography - Saraste, Antti; Knuuti, Juhani (Elsevier BV, 2026)
Total-body positron emission tomography (PET) systems with a long axial field of view (LAFOV) are now commercially available and represent the state of the art in PET imaging. These systems provide wide anatomical coverage and markedly increased detection sensitivity. Clinical studies have demonstrated enhanced image quality, superior quantification, and benefits for tracer kinetic modeling through dynamic imaging. LAFOV PET/CT allows for substantial reductions in acquisition time and radiation dose while maintaining diagnostic image quality. Full-body coverage enables dynamic whole-body imaging, which enables tracer kinetic modeling across multiple organs and the large vascular structures, offering new opportunities for studying their interactions in cardiovascular and systemic diseases. Furthermore, these systems facilitate the development of new PET methods including pharmacokinetics of new tracers. This review discusses the emerging opportunities and challenges associated with the application of LAFOV PET/CT systems in cardiovascular diseases.